Teknik Pemeriksaan Magnetic Resonance Imaging (MRI) Brain Dengan Penambahan Sequence Axial 3D-Fiesta Pada Kasus Facial Tic - Ameliya Widya Astuti; I Made Lana Prasetya; Teguh Hariyanto (Compromise Journal Community Proffesional Service Journal, 2023)
Magnetic Resonance Imaging is a medical device that combines computer technology, strong magnetic fields and radio waves to emulate representations of human body parts and produce more detailed and clear images, one of which is Facial Tic on the Brain. The MRI Brain examination aims to see the anatomy and abnormalities in the brain. This study aims to determine the MRI Brain examination procedure and the role of the Axial 3D Fiesta sequence in cases of Facial Tic. Use of the 3D Fast Imaging Employing Steady State Acquisition (FIESTA) sequence for evaluation of the head nerves. The research method used is descriptive research with a case study approach. Data collection was carried out from July 2023 to August 2023 using a GE 1.5 Tesla MRI aircraft. The subject consisted of a patient with clinical Facial Tic. Data collection was carried out through observation, interviews and documentation. The research results were obtained according to theory using sagittal T1, Coronal PD/T2, Axial PD/T2/T1/FLAIR/EPI, Axial 3D incoherent GRE T1, Axial/oblique SE MT, Axial DWI, Diffusion Tensor Imaging (DTI), Axial perfusion sequences. imaging, while in the field using localizer sequences, Axial DWI, Axial T2 Flair, Axial T2, Axial T1, Axial T2* GRE, Sagittal T1, Coronal T2, and Axial 3D Fiesta